Comparison of two cohorts of patients presenting with AIDS: patients with previously known HIV diagnoses and true late presenters. Issue 7 (22nd May 2013) - Lee, MJ; Rayment, M; Scourfield, A; Gazzard, B
Abstract : Objectives: We aimed to identify the factors associated with developing AIDS 6 months or more after an HIV diagnosis, and to examine how post-HIV diagnosis AIDS (PHDA) patients differed from true late presenters (HIV diagnosed concurrent with the first AIDS presenting event) in their demographics and comorbidities. Methods: A retrospective analysis was undertaken of all inpatients admitted to a large HIV unit presenting with the following AIDS-defining infections: cryptococcal meningitis, cerebral toxoplasmosis or Pneumocystis jirovecii pneumonia between 1 January 2005 and 31 December 2010. Results: 114 HIV-positive patients presented with AIDS-defining infections. Compared with late presenters, PHDA patients had a larger proportion of migrants and visitors (53.7% vs 34.0%, p=0.047), were more likely to inject drugs (9.3% vs 0.0%, p=0.032), had more previous HIV-associated diseases (57.4% vs 12.8%, p=0.000), psychiatric comorbidities (35.2% vs 12.8%, p=0.009), rates of alcohol abuse (24.1% vs 4.3%, p=0.005) and reported social issues (25.9% vs 0.00%, p=0.000). 88.9% of PHDA patients were lost to follow-up for a period of at least 4 months since diagnosis. Common reasons for clinic non-attendance included travel, social issues, transfer of care and treatment avoidance. Common reasons for antiretroviral treatment breaks included drug side effects, negative beliefs about medication, incompatible lifestyles and social issues. Conclusions: Compared with late presenters, PHDA patients demonstrate clear demographical differences including higher rates of psychiatric comorbidities, social issues, alcohol and substance abuse. Many PHDA patients default follow-up. The retention of HIV patients in care and on treatment must be addressed by clinicians to prevent avoidable morbidity.